Mochras borehole revisited: a new global standard for Early Jurassic earth history - Hesselbo, S. P. (2013)
The Early Jurassic epoch was a time of extreme environmental change: there are well-documented examples of rapid transitions from cold, or even glacial, climates to super greenhouse events, the latter characterized worldwide by hugely enhanced organic carbon burial, multiple large isotopic anomalies, global sea-level change, and mass extinction (Price, 1999; Hesselbo et al., 2000; Jenkyns, 2010; Korte and Hesselbo, 2011). These icehouse–greenhouse events not only reflect changes in the global climate system but are also thought to have had significant influence on the evolution of Jurassic marine biota (e.g. van de Schootbrugge et al., 2005; Fraguas et al., 2012). Furthermore, the events may serve as analogues for present-day and future environmental transitions. Although our knowledge of specific global change events within the Early Jurassic is rapidly improving, such as the Toarcian oceanic anoxic event (or T-OAE), we still do not have a comprehensive understanding of the timing, pacing, or triggers for these environmental perturbations, principally because of the temporally fragmentary nature of the existing data sets. The major goal for this proposed ICDP project is therefore to produce a new global standard for these key 25 million years of earth history by re-drilling and doublecoring a 45 yr old borehole at Mochras Farm on the edge of Cardigan Bay, Wales, and developing an integrated stratigraphy for the cored material. The new data sets will be applied to understand fundamental questions about the longand short-term evolution of the earth system. Cycles that occur regionally and that provisionally appear in the Mochras logs will allow evaluation of the extent to which major environmental change events are astronomically forced, resulting from internal system dynamics, or are triggered by deepearth processes.